2015
DOI: 10.1107/s2053230x15004343
|View full text |Cite
|
Sign up to set email alerts
|

Complex assembly, crystallization and preliminary X-ray crystallographic analysis of the human Rod–Zwilch–ZW10 (RZZ) complex

Abstract: The 800 kDa complex of the human Rod, Zwilch and ZW10 proteins (the RZZ complex) was reconstituted in insect cells, purified, crystallized and subjected to preliminary X-ray diffraction analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The high-resolution cryo-EM structure of the RZZ complex reported here crowns a succession of studies that began with the biochemical reconstitution and bioinformatic analysis of RZZ subunits, the determination of the crystal structure of Zwilch, and the report of a low-resolution EM reconstruction of the RZZ (Altenfeld et al, 2015;Civril et al, 2010;Mosalaganti et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The high-resolution cryo-EM structure of the RZZ complex reported here crowns a succession of studies that began with the biochemical reconstitution and bioinformatic analysis of RZZ subunits, the determination of the crystal structure of Zwilch, and the report of a low-resolution EM reconstruction of the RZZ (Altenfeld et al, 2015;Civril et al, 2010;Mosalaganti et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Reconstitution and structural analysis of the RZZ complex Using reconstituted human RZZ (Altenfeld et al, 2015;Mosalaganti et al, 2017), we previously reported a single particle cryo-EM reconstruction of the RZZ at an overall resolution of ~10-12 Å (1 Å = 0.1 nm). As only the structure of Zwilch (Civril et al, 2010) (PDB ID 3IF8) had been experimentally determined, we had tried to account for the observed density by building ad hoc homology models of ROD or ZW10 and fitting them in the 3D reconstruction (Mosalaganti et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We generated recombinant versions of the human RZZ complex and of several RZZ variants (including fluorescently tagged versions and deletion mutants) by baculovirus-driven insect cell expression ( Fig. 1 C; see the Expression and purification of RZZ section of Materials and methods; Altenfeld et al, 2015). Sedimentation velocity analytical ultracentrifugation (AUC) of recombinant RZZ showed a single peak with a predicted molecular mass of 813 kD, very close to the theoretical mass of 812 kD calculated by assuming a 2:2:2 stoichiometry, confirming and extending less precise previous measurements Çivril et al, 2010).…”
Section: Reconstitution and Structural Analysis Of The Rzz Complexmentioning
confidence: 99%
“…A protocol for the expression of RZZ has been described previously (Altenfeld et al, 2015). For a pellet of 500 ml of expression culture, cell lysis was performed in 100 ml lysis buffer (50 mM Hepes, pH 8.5, 200 mM NaCl, 10% glycerol, 20 mM imidazole, 5 mM βMe, 1 mM PMSF, and 1 mM protease inhibitor cocktail) by sonication.…”
Section: Expression and Purification Of Rzzmentioning
confidence: 99%
See 1 more Smart Citation